Financial Literacy and Self-Control on Financial Security: The Mediating Role of Financial Behavior - Sofiana Kartika Dewi; Muhammad Ali Fikri; Tina Sulistiyani; Made Galih Wisnu Wardana (Journal of Economics, Social, and Humanities, 2025)
Dynamic developments encourage individuals to have the ability and knowledge to manage finances. Financial literacy and self-control in individuals enhance financial behavior and financial security. This study aims to analyze the influence of financial literacy and self-control on financial security with financial behavior as a mediator. The research sample consists of 106 respondents from Generation Z in Yogyakarta, Indonesia. Statistical analysis used a structural equation model with Smart Partial Least Square version 4.0. The results of this study indicate that financial literacy has a positive effect on financial behavior, financial literacy has a positive impact on financial security, self-control does not have a positive effect on financial behavior, self-control does not influence financial security, financial behavior has a positive impact on financial security, financial behavior does not mediate the positive influence of financial literacy on financial security, and financial behavior does not mediate the positive influence of self-control on financial security.